Antenna-in-package design for wirebond interconnection to highly integrated 60-GHz radios - Wai, L. L. (2010)
This paper first presents a quasi-cavity-backed, guard-ring-directed, substrate-material-modulated slot antenna. The antenna, intended for use in highly integrated 60-GHz radios, is deliberately designed to exhibit capacitive input impedance to suit low-cost wire-bonding packaging and assembly technique.